TRIAGE-STROKE: Treatment strategy In Acute larGE vessel occlusion: Prioritize IV or endovascular treatment—A randomized trial. Issue 1 (January 2020) - Behrndtz, Anne; Johnsen, Søren P; Valentin, Jan B; Gude, Martin F; Blauenfeldt, Rolf A; Andersen, Grethe; Majoie, Charles BLM; Fisher, Marc; Simonsen, Claus Z
Rationale: For patients with acute ischemic stroke and large vessel occlusions, intravenous thrombolysis and endovascular therapy are standard of care, but the effect of endovascular therapy is superior to intravenous thrombolysis. If a severe stroke with symptoms indicating large vessel occlusions occurs in the catchment area of a primary stroke center, there is equipoise regarding optimal transport strategy. Aim: For patients presenting with suspected large vessel occlusions (PASS ≥ 2) and a final diagnosis of acute ischemic stroke, we hypothesize that bypassing the primary stroke center will result in an improved 90-day functional outcome. Sample size: We aim to randomize 600 patients, 1:1. Design: A national investigator-driven, multi-center, randomized assessor-blinded clinical trial. The Prehospital Acute Stroke Severity Scale has been developed. It identifies most patients with large vessel occlusions in the pre-hospital setting. Patients without a contraindication for intravenous thrombolysis are randomized to either transport directly to a comprehensive stroke centers for intravenous thrombolysis and of endovascular therapy or to a primary stroke center for intravenous thrombolysis and subsequent transport to a comprehensive stroke centers for of endovascular therapy, if needed. Outcomes: The primary outcome will be the 90-day modified Rankin Scale score (mRS) for all patients with acute ischemic stroke. Secondary outcomes include 90-day mRS for all randomized patients, all patients with ischemic stroke but without large vessel occlusions, and patients with hemorrhagic stroke. The safety outcomes include severe dependency or death and time to intravenous thrombolysis for ischemic stroke patients. Discussion: Study results will influence decision making regarding transport strategy for patients with suspected large vessel occlusions.